The interplay of colour and bioacoustic traits in the differentiation of a Southeast Asian songbird complex - Chyi Yin Gwee; Qiao Le Lee; Simon P. Mahood; Hung Le Manh; Robert Tizard; Krairat Eiamampai; Philip D. Round; Frank E. Rheindt (Molecular Ecology, 2021)
Morphological traits have served generations of biologists as a taxonomic indicator, and have been the main basis for defining and classifying species diversity for centuries. A quantitative integration of behavioural characters, such as vocalizations, in studies on biotic differentiation has arisen more recently, and the relative importance of these different traits in the diversification process remains poorly understood. To provide a framework within which to interpret the evolutionary interplay between morphological and behavioural traits, we generated a draft genome of a cryptic Southeast Asian songbird, the limestone wren‐babbler Napothera crispifrons . We resequenced whole genomes of multiple individuals of all three traditional subspecies and of a distinct leucistic population. We demonstrate strong genomic and mitochondrial divergence among all three taxa, pointing to the existence of three species‐level lineages. Despite its great phenotypic distinctness, the leucistic population was characterized by shallow genomic differentiation from its neighbour, with only a few localized regions emerging as highly diverged. Quantitative bioacoustic analysis across multiple traits revealed deep differences especially between the two taxa characterized by limited plumage differentiation. Our study demonstrates that differentiation in these furtive songbirds has resulted in a complex mosaic of colour‐based and bioacoustic differences among populations. Extreme colour differences can be anchored in few genomic loci and may therefore arise and subside rapidly.

Overexpressing ovotransferrin and avian β-defensin-3 improves antimicrobial capacity of chickens and poultry products - Caitlin A. Cooper; Mark L. Tizard; Tamsyn Stanborough; Sean C. Moore; P. Scott Chandry; Kristie A. Jenkins; Terry G. Wise; Terri E. O’Neil; Daniel S. Layton; Kirsten R. Morris; Robert J. Moore; Narelle Fegan; et al. (Transgenic Research, 2019)

Genetic and biometric variation across the fragmented range of Jerdon’s Babbler, Chrysomma altirostre, a threatened Oriental grassland specialist - Keren R. Sadanandan; Urban Olsson; Robert Tizard; Aleem A. Khan; Thet Zaw Naing; Naing Lin; Nila Pwint; Frank E. Rheindt (Journal of Ornithology, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Biodiversity Conservation in a Changing Climate: A Review of Threats and Implications for Conservation Planning in Myanmar - Madhu Rao; Saw Htun; Steven G. Platt; Robert Tizard; Colin Poole; Than Myint; James E. M. Watson (Ambio, 2013)